Research synthesis in veterinary science: Narrative reviews, systematic reviews and meta-analysis. Issue 3 (December 2015) - O'Connor, Annette; Sargeant, Jan
Highlights: Combining research enables end-users to understand a body of scientific literature. Research synthesis is a unique research endeavor. A literature review is an output of research synthesis science. Systematic reviews are a type of literature review. Bias reduction tools should be used to reduce bias in reviews to increase validity. Abstract: Reviews of the scientific literature are critically important for synthesizing the state of knowledge and are used extensively in teaching, clinical practice and public policy. Despite the importance of literature reviews, in veterinary science little attention has been paid to the science of research synthesis. In the same manner that diverse study designs address diverse research questions, different approaches to combining scientific literature serve different and valid purposes. However, and again reflective of the underlying primary research, the potential for bias in a review should also be considered when interpreting the results. This article introduces some basic concepts in research synthesis and discusses some of the basic forms of reviews including narrative reviews, systematic reviews and meta-analysis. Also discussed are potential sources of bias and design features that can be incorporated into reviews to either reduce, or at least acknowledge, the potential for bias.